2019
DOI: 10.1093/mnras/stz2544
|View full text |Cite
|
Sign up to set email alerts
|

The VANDELS survey: the star-formation histories of massive quiescent galaxies at 1.0 < z < 1.3

Abstract: We present a Bayesian full-spectral-fitting analysis of 75 massive ($M_* \gt 10^{10.3} \, \mathrm{M_\odot }$) UVJ-selected galaxies at redshifts of 1.0 < z < 1.3, combining extremely deep rest-frame ultraviolet spectroscopy from VANDELS with multiwavelength photometry. By the use of a sophisticated physical plus systematic uncertainties model, constructed within the bagpipes code, we place strong constraints on the star-formation histories (SFHs) of individual objects. We first constrain the stellar mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
109
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 145 publications
(286 reference statements)
28
109
2
Order By: Relevance
“…The double power-law model used in the initial fits has been shown to work well for quiescent galaxies (Carnall et al 2019a). However, it only allows a single rise and fall in star formation over time.…”
Section: Two Component Model For Post-starburst Galaxiesmentioning
confidence: 98%
“…The double power-law model used in the initial fits has been shown to work well for quiescent galaxies (Carnall et al 2019a). However, it only allows a single rise and fall in star formation over time.…”
Section: Two Component Model For Post-starburst Galaxiesmentioning
confidence: 98%
“…While recent spectroscopic surveys have collected larger samples of quiescent galaxies at higher redshifts (e.g. Pacifici et al 2016;Thomas et al 2017;Carnall et al 2019a;Estrada-Carpenter et al 2019), there has not yet been a systematic study of the SFHs with environment. We can significantly improve our understanding of the differences in SFHs of galaxies related to their environment with the Gemini Observations of Rich Early ENvironments survey (GOGREEN 1 ; Balogh et al 2017, Balogh et al 2020in prep.).…”
Section: Take Down Policymentioning
confidence: 99%
“…In fitting the spectroscopy and photometry together, we need to account for uncertainties in the spectral response calibration, and for the overall flux calibration due to slit losses. Several authors have demonstrated the challenge of simultaneously fitting spectral and photometric data, especially when the spectral continuum is not well characterised (Panter et al 2007;van der Wel et al 2016;Belli et al 2019;Carnall et al 2019a;Johnson et al 2019). As described in Section 2.2, the spectra were not absolute flux calibrated.…”
Section: Fitting Star Formation Histories Of Quiescent Galaxiesmentioning
confidence: 99%
See 2 more Smart Citations